Immediately scheduled for an appointment to smoking cessation clinics: Key to quitting smoking in chronic airway disease – a multicenter randomized study - Dilek Karadoğan; Tahsin Gökhan Telatar; İlknur Kaya; Siahmet Atlı; Neslihan Köse Kabil; Feride Marım; Merve Yumrukuz Şenel; Aycan Yüksel; Burcu Yalçın; Ökkeş Gültekin; Merve Erçelik; Metin Akgün (Tobacco Induced Diseases)
Introduction A significant proportion of patients with chronic airway diseases continue to smoke even after the diagnosis. In addition, smoking cessation support continues to be a neglected issue in real-life settings by physicians for that patient group. Therefore, in our search for a solution to this issue, we conducted our study to evaluate the effect of arranging immediate appointments to smoking cessation outpatient clinics on smoking cessation success in patients with chronic airway disease.